ABSENTEÍSMO E COMPROMETIMENTO: NOVAS REFLEXÕES A PARTIR DE UM ESTUDO DE CASO ANALISADO SOB A ÓTICA DA PSICODINÂMICA DO TRABALHO - Maria Irene Stocco Betiol; Maria José Tonelli (Ação Ergonômica)
This paper presents the results of a case study carried out in a large-scale Brazilian company, of the services sector, and the objective was to comprehend the questions of absenteeism and commitment at work. Using the Psychodynamics of Work (Dejours, 1994) as a theoretic referential, focus group with shop floor workers were carried out, in order to comprehend the expectations of the performance of their work. The research showed the work organization, in its concrete and symbolic aspects, caused suffering, dissatisfaction and fears that led to the lack of commitment and absenteeism.